Analisis Investasi Online Perspektif Ekonomi Syariah - Syamsuddin; Abbas, Ngatmin (Journal of Islamic Economic and Law (JIEL), 2024)
Online investment has gained popularity in the digital age, but a major challenge is ensuring that such investments comply with Islamic economic principles. Islamic economics emphasizes the prohibition of riba (interest), gharar (excessive uncertainty), and maysir (gambling) in all forms of investment. This study aims to analyze the extent to which online investments adhere to Islamic economic principles and to provide practical guidance for Muslim investors in selecting compliant investment products. The research employs a library research method by gathering data from various literature sources relevant to Islamic economic principles and online investment practices. The collected data is analyzed to evaluate the compliance of online investments with Sharia principles. The findings reveal that while online investments offer convenience and flexibility, many investment products do not fully comply with Sharia principles. This study discusses key elements such as transparency, fairness, and risk, and provides guidance for choosing investments that align with Islamic economic principles. The study identifies that online investments must be free from riba, gharar, and maysir to be considered Sharia-compliant. Additionally, it is crucial for investors to verify legality, monitor transparency, and consult with Sharia experts.